Does intraoperative bone density testing correlate with parameters of primary implant stability? A pilot study in minipigs - Tanja Grobecker‐Karl; Victor Palarie; Sonja Schneider; Matthias Karl (Wiley, 2019)
Abstract Objectives Bone density, surgical protocol, and implant design are the major determinants of primary stability. The goal of this animal trial was to investigate potential correlations of intraoperative bone density testing with clinical and histologic parameters of primary implant stability. Material and methods Following extractions of all mandibular premolars and subsequent healing, four implants each were placed in a total of four minipigs. Bone density was determined by applying intraoperative compressive tests using a device named BoneProbe whereas measurements of implant insertion torque and resonance frequency analysis were used for evaluating implant stability. Bone mineral density (BMD) and bone to implant contact were quantified after harvesting mandibular block sections. Spearman rank correlation tests were performed for evaluating correlations (α = .05). Results Due to variation in clinical measurements, only weak correlations could be identified. A positive correlation was found between the parameters bone to implant contact and BMD (Spearman's rho .53; p = .05) whereas an inverse correlation was observed between BMD and implant stability (Spearman's rho −.61; p = .03). Both BoneProbe measurements in the cortical and trabecular area positively correlated with implant insertion torque (Spearman's rho 0.60; p = .02). A slightly stronger correlation was observed between the average of both BoneProbe measurements and implant insertion torque (Spearman's rho.66; p = .01). Conclusions While establishing exact relationships among parameters of implant stability and the measurement techniques applied would require greater sample size, intraoperative compressive testing of bone might, despite the weak correlations seen here, be a useful tool for predicting primary implant stability.